School-Based Assessment in Secondary School Science Learning: Teachers’ Perspective - Nwafor, Stephen Chinedu; Awosika, Opeyemi Fadekemi; Okoye, Grace Nwakaego (Universitas Pendidikan Indonesia (UPI), 2024)
The study established the teachers' viewpoints on school-based assessment of secondary school science instruction in Anambra State, Nigeria. The research used a descriptive survey methodology. The 158 science teachers employed by the 32 public secondary schools in the Onitsha Education Zone of Anambra State made up the population of the study. Two of the three Local Government Areas of the Zone were chosen using the purposeful sampling technique, and the sample size was all 158 science teachers.